He himself is a perfect, words are remarkable poet - Khilola Abdujabbarova (Peerian Journals Publishing, 2022)
In this article, Erkin Vohidov was reflected as a poet and statesman. It was revealed that his political and philosophical views are also relevant for the current period. Particular attention was paid to the fact that its human qualities, in particular, strive for perfection as a person
Keywords: man; perfection; poet; statesman